ChemInform Abstract: Three New Resin Glycosides and a New Tetrahydropyran Derivative from the Seeds of Quamoclit pennata. Issue 4 (31st January 2013) - Ono, Masateru; Takaki, Yoshinari; Takatsuji, Masamitsu; Akiyama, Kousuke; Okawa, Masafumi; Kinjo, Junei; Miyashita, Hiroyuki; Yoshimitsu, Hitoshi; Nohara, Toshihiro
Abstract [isolation and structure determination of four new resin glycosides quamoclins V—VII [cf.